Structures and Electronic Properties of Graphene with Vacancy Defects. Issue 1658 (22nd May 2014) - Sugimoto, J.; Shintani, K.
ABSTRACT: The structures and electronic properties of graphene with defects consisting of one to six atomic vacancies are investigated using first-principles calculation. All of the geometrically possible initial structures of a movacancy or a multivacancy in graphene are equilibrated. The formation energies and electronic band structures for the equilibrated defective structures are calculated. It is suggested non-zero bandgaps may be induced in graphene by introducing some types of monovacancy or multivacancy although further checks regarding supercell size are necessary to ensure the present results.